Propolis effect on Th1/Th2 cytokines production by acutely stressed mice - Pagliarone, Ana Carolina [UNESP]; Missima, Fabiane [UNESP]; Orsatti, Claudio Lera [UNESP]; Bachiega, Tatiana Fernanda [UNESP]; Sforcin, Jose Mauricio [UNESP] (Elsevier B.V., 2009)
Aim of the study: Propolis has gained special attention due to its biological properties, however, little is known about its immunomodulatory effects in stress conditions. The purpose of this study was to investigate propolis effect on Th1/Th2 cytokines production by spleen cells of acutely stressed mice. Serum corticosterone concentration was determined as a stress indicator.Materials and methods: Male BALB/c mice were submitted to restraint stress and treated with propolis (200 mg/kg) for 3 days. Supernatants of splenocytes cultures were assessed for Th1/Th2 cytokines determination.Results: Regarding Th1 cytokines production, no alterations were seen in IL-2 production; however, IFN-gamma production was inhibited in stressed mice, even when treated with propolis. As to Th2 cytokines, IL-4 was inhibited in stressed mice, but normal levels were seen when these animals were treated with propolis. No significant differences were found in IL-10 production between the experimental groups. Stressed groups (treated or not with propolis) showed higher corticosterone concentrations in comparison to control group.Conclusions: Data suggest that propolis treatment was not able to counteract the stress-induced immunosuppressive effect on IFN-gamma production; however, propolis showed an immunorestorative role, increasing IL-4 production in stressed mice, favoring humoral immune response during stress. Since the exact mechanisms of this natural product on immune system are still unclear, further studies are still required for a better comprehension of propolis use as a therapeutic alternative against the stress-induced negative effects that could lead to the development of various diseases. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Propolis; Stress; Th1/Th2 cytokines; Immunomodulation